EFFECTIVE AND MODERN METHODS OF TEACHING ENGLISH AND OTHER FOREIGN LANGUAGES - Sokhiba Kholdarova Gulomjon kizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
Great attention is paid to learning a foreign language in the world. It is very important to learn and teach a foreign language quickly and conveniently. This article covers some of the world's tried and true ways of teaching English effectively and some modern educational technologies in language learning. The article provides examples of the methods used by language teaching specialists in practice.